Website-Based Interactive Multimedia to Improve Students’ Learning Independence on Natural Resources Material in Grade IV Elementary School: Indonesia - Indra Pastika I Komang; I Gusti, Agung Ayu Wulandari; I Made, Citra Wibawa (Jurnal Media dan Teknologi Pendidikan, 2025)
This research is motivated by the low level of learning independence which has an impact on the low learning outcomes of students. This is caused by the lack of use of innovative and creative learning media that can increase motivation and learning independence. This study aims to develop website-based interactive multimedia on natural resources material that is valid, practical and effective for increasing the learning independence of students in grade IV SD. This type of research is research and development (R&D) with the ADDIE development research model. The subjects in this study were 3 experts, 2 teachers. The test subjects of this study were grade IV students totaling 30 people. This study used a quasi-experimental design of one group pre-test-post test. Data collection methods are observation, interviews, questionnaires / surveys, and tests. The instruments used in data collection are learner independence questionnaire sheets and interviews. The data analysis technique used is descriptive quantitative and descriptive qualitative. The results showed that there was a significant difference in students' learning independence before and after using website-based interactive multimedia. It can be concluded that, website-based interactive multimedia media innovation is effective in increasing students' learning independence. The results of this study have implications for increasing students' learning independence and increasing digital skills in utilizing interactive multimedia.